Phytochemical Investigation of Crotalaria Species-Isolation of a New Dihydro Chalcone from Crotalaria ramosissima - V. Namratha (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
Natural products once served as the only source of medicines to mankind. Plants often synthesize unexpected novel structures which are biologically active, by various biosynthetic pathways. Phytochemical analysis of medicinal plants revealed the presence of various chemical constituents like alkaloids, flavonoids, Saponins, Glycosides, Triterpenoids, which possess a wide range of Pharmacological activity. The Genus Crotalaria, family fabaceae includes 500 species distributed in tropical and subtropical regions and can be used as medical folklore remedies for treating different health disorders. Several flavones, chalcones and Chromeno chalcones have been isolated from these genus. A detailed re-investigation of Crotalaria ramisissima resulted in the isolation of a new dimethyl, dihydro chalcone Crotaramin, whose structure elucidation was determined by 2D spectral methods.